Deep interventions for a sustainable transport future - Stephenson, J; Spector, S; Hopkins, D; McCarthy, A (Elsevier, 2017)
The dominance of automobility is giving rise to unsustainable outcomes, not least of which is its contribution to climate change. At the same time, business-as-usual transport systems are entering a period of turbulence as a result of influences such as new and disruptive technologies, intelligent systems, new business models, changing consumer expectations, population growth, suburban sprawl, and national commitments to reduce greenhouse gas emissions. An optimal trajectory towards sustainable transport is unlikely to be achieved in a laissez-faire policy environment, and nor is it likely that it will be resolved by any single solution. Rather, it is likely to require carefully crafted interventions that have a good fit with unique national circumstances, and which will work in an integrated way to achieve change consistently throughout the transport system. The research reported in this paper draws on the situated knowledge and experience of New Zealand transport experts to develop a suite of potential interventions for a sustainable transport future for New Zealand. Drawing on the findings of a four-stage Delphi study, which solicited experts’ views on interventions that could lead to better outcomes than were being achieved by the current policy environment. The paper concludes that a consistent and integrated commitment is required at all levels of governance and across all parts of the transport system to transition away from automobility and towards sustainable mobility.